Optimization of the efflux ratio and permeability of covalent irreversible BTK inhibitors. Issue 20 (1st November 2018) - Qiu, Hui; Liu-Bujalski, Lesley; Caldwell, Richard D.; Viacava Follis, Ariele; Gardberg, Anna; Goutopoulos, Andreas; Grenningloh, Roland; Head, Jared; Johnson, Theresa; Jones, Christopher C.V.; Jones, Reinaldo; Mochalkin, Igor; et al.
Graphical abstract: Highlights: A novel series of covalent Btk inhibitors was discovered. Hit molecules showed high ER. Optimization of ER led to the discovery of the lead molecule. Abstract: Bruton's tyrosine kinase (Btk) is a member of the Tec kinase family that is expressed in cells of hematopoietic lineage (e.g. B cells, macrophages, monocytes, and mast cells). Small molecule covalent irreversible Btk inhibitors targeting Cys481 within the ATP-binding pocket have been applied in the treatment of B-cell malignancies. Starting from a fragment, we discovered a novel series of potent covalent irreversible Btk inhibitors that bear N -linked groups occupying the solvent accessible pocket (SAP) of the active site of the Btk kinase domain. The hit molecules, however, displayed high P-gp mediated efflux ratio (ER) and poor A-B permeability in Caco-2 assay. By decreasing tPSA, installing steric hindrance and adjusting clogP, one top molecule9 was discovered, which showed a 99% decrease in efflux ratio and a 90-fold increase in A-B permeability compared to hit molecule1 .